Public sector strategy design theory and practice for government and nonprofit organizations - McNabb, David E.; Lee, Chung-Shing (Routledge, 2021)
Within the public sector, strategies are not designed to influence markets, but instead to guide operations within a complex environment of multilateral power, influence, bargaining, and voting. In this book, authors David McNabb and Chung-Shingh Lee examine five frameworks public sector organization managers have followed when designing public sector strategies. Its purpose is to serve as a guide for managers and administrators of large and small public organizations and agencies. This book is the product of a combined more than sixty years of researching, teaching and leading organizational seminars on the theory and practice of management applications in industrial, commercial, nonprofit and public sector organizations.